Novel terpolymers and their use in pharmaceutical dosage forms - Patents.com

JP7635299B2Active Publication Date: 2025-02-25BASF SE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023095944
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-12-20
Filing Date
2023-06-12
Publication Date
2025-02-25
Estimated Expiration
2038-12-07

Smart Images

  • Figure 0007635299000001
    Figure 0007635299000001
  • Figure 0007635299000002
    Figure 0007635299000002
  • Figure 0007635299000003
    Figure 0007635299000003
Patent Text Reader

Abstract

To provide excipients for pharmaceutical formulations that allow for a safe and efficient stabilization against recrystallization and precipitation from the supersaturated state after in vivo release of sparingly water-soluble active ingredients in the aqueous environment of the human or animal body in order to assure bioavailability.SOLUTION: There is provided a terpolymer, wherein 20 to 35 wt.% of the structural units are derived from acrylic acid, 45 to 60 wt.% of the structural units are derived from a hydrophobic methacrylate selected from a group consisting of isopropyl methacrylate, tert-butyl methacrylate and cyclohexyl methacrylate and 15 to 35 wt.% of the structural units are derived from a third olefinic monomer selected from the group consisting of N-vinyl lactam, hydroxy ethyl methacrylate and phenoxyethyl acrylate with the proviso that the total amount of structural units derived from the three monomer groups adds up to 100 wt.%, and wherein the terpolymer is partly neutralized to give a pH in the range of 5 to 9 upon dissolution in water.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to novel terpolymers based on acrylic acid, a hydrophobic methacrylate and a third olefin monomer, their use as pharmaceutical excipients to improve gastrointestinal adsorption, respective pharmaceutical dosage forms, and methods for making the terpolymers. [Background technology]

[0002] Intestinal absorption of poorly water-soluble drugs (BCS classes II and IV) is limited by the maximum concentration achievable in the gastrointestinal lumen. Thus, various approaches in formulation development aim at increasing the dissolution rate in the gastrointestinal tract and improving drug solubility. Administering the drug as a solution is a common approach to enhance the intestinal absorption of poorly water-soluble drugs. For this purpose, hydrophobic drugs are formulated using mixtures of cosolvents, surfactants, complexing agents (e.g., cyclodextrins) and / or oils. After oral administration, these formulations increase the total concentration of the drug present in solution; however, this approach does not necessarily result in improved bioavailability. Depending on the lipophilicity of the drug, a large portion of the drug molecules is solubilized in a mixture of colloidal species (e.g., emulsified oils, micelles, etc.). This portion is not available for absorption, since only the free molecular species of the drug can penetrate the intestinal barrier. Furthermore, dilution and dispersion of the formulation in the gastrointestinal tract reduces the solubilization capacity. As a result, a metastable supersaturated state is created, which ultimately leads to the precipitation of the drug.

[0003] Besides administration in solution, there are several formulation strategies that allow the delivery of poorly water-soluble drugs in solid form. These approaches aim to generate high-energy or rapidly dissolving forms of the drug that induce supersaturation in the gastrointestinal tract (e.g., by milling, co-grinding, solvent evaporation, melting, or crystal engineering). For example, poorly water-soluble drugs can be produced into solid dispersions (e.g., by spray drying or hot melt extrusion) in combination with suitable polymers (e.g., polyvinylpyrrolidone, vinylpyrrolidone-vinyl acetate copolymers, polyethylene glycols, polymethacrylates, cellulose derivatives, etc.) and / or surfactants. These contain amorphous drug particles embedded in a polymer matrix that stabilizes the amorphous state by vitrification, specific drug-polymer interactions, and / or reduced mobility. The release of the embedded drug molecules often depends on the dissolution rate of the polymer matrix. After dissolution of the dosage form in the gastrointestinal tract, the concentration of the drug in solution exceeds the saturation solubility. This supersaturated state is thermodynamically unstable, and the system tends to return to equilibrium by precipitation of the drug.

[0004] To benefit from the increased concentration, it is necessary to stabilize the supersaturated state in the gastrointestinal lumen for a sufficient time for absorption. For example, cellulose derivatives (e.g., HPMC or HPMCAS) and vinyl polymers (e.g., polyvinyl alcohol, polyvinylpyrrolidone, or vinylpyrrolidone-vinyl acetate copolymers) have been described to inhibit drug precipitation by preventing nucleation and / or crystal growth. It is important to note that this type of stabilization is different from the stabilization of the amorphous state in the dosage form prior to application.

[0005] WO2014 / 159748 refers to the use of an acrylate-based crystallization inhibitor, preferably a copolymer of butyl methacrylate, 2-dimethylaminoethyl methacrylate and methyl methacrylate in a weight ratio of 1:2:1.

[0006] WO 2005 / 058383 describes adhesive implants for body wall repair comprising water-soluble biocompatible polymers with adhesive properties, which are alkyl acrylates such as octyl acrylate and copolymers based on acrylic acid and hydroxyalkyl (meth)acrylates.

[0007] WO 2014 / 182713 relates to statistical copolymers made from at least three different acrylate monomers, such as alkyl (meth)acrylate, carbalkoxyalkyl (meth)acrylate, hydroxyalkyl (meth)acrylate and alkyl acetyl acrylate, and their use to inhibit drug crystallization and supersaturation maintenance. WO 2014 / 182710 refers to similar copolymers further substituted with sugar moieties. These copolymers exhibit several disadvantages. First, all monomer groups are not readily available and need to be specially synthesized. Another problem is that the copolymers have a rather low glass transition temperature, which makes spray drying difficult. A lower glass transition temperature is also disadvantageous in terms of storage stability, since the dosage form tends to undergo so-called "cold flow". Sugar-substituted copolymers also exhibit instability when processed by melt extrusion.

[0008] According to the prior art, cellulose derivatives such as HPMCAS are often considered as the excipient of choice to inhibit drug precipitation [J. Brouwers, ME Brewster, P. Augustijns, Supersaturating drug delivery systems: The answer to solubility-limited oral bioavailability? Journal of Pharmaceutical Sciences, 98 (2008) 2549-2572; DB Warren, H. Benameur, CJH Porter, CW Pouton, Using polymeric precipitation inhibitors to improve the absorption of poorly water-soluble drugs: A mechanistic basis for utility, Journal of Drug Targeting, 18 (2010) 704-731; S. Baghel, H. Cathcart, NJ O'Reilly, Polymeric amorphous solid dispersions: A review of amorphization, crystallization, stabilization, solid-state characterization, and aqueous solubilization of biopharmaceutical classification system class II drugs, Journal of Pharmaceutical Sciences, 105 (2016) 2527-2544]. However, the effectiveness of HPMCAS and other known polymers is often not ideal because these polymers were originally optimized for other applications (e.g., coatings or thickeners). So far, no excipients are available that meet all the requirements regarding variability, long-term stability, processability and performance. Summary of the Invention [Problem to be solved by the invention]

[0009] The problem to be solved by the present invention was to develop excipients for pharmaceutical formulations that allow safe and efficient stabilization of poorly water-soluble active ingredients against recrystallization and precipitation from supersaturated conditions after in vivo release in the aqueous environment of the human or animal body in order to ensure sufficient bioavailability. [Means for solving the problem]

[0010] This problem has been solved by finding a terpolymer having i) 20-35% by weight of the structural units derived from acrylic acid, ii) 45-60% by weight of the structural units derived from a hydrophobic methacrylate, and iii) 15-40% by weight of the structural units derived from a third olefin monomer selected from the group consisting of N-vinyl lactam, hydroxyethyl methacrylate, and phenoxyethyl acrylate, with the proviso that the sum of i), ii) and iii) equals 100% by weight. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] According to a preferred embodiment, the invention relates to a terpolymer in which i) 20-35% by weight of the structural units are derived from acrylic acid, ii) 45-60% by weight of the structural units are derived from hydrophobic methacrylates, and iii) 15-40% by weight of the structural units are derived from a third olefin monomer selected from the group consisting of N-vinyllactam, hydroxyethyl methacrylate and phenoxyethyl acrylate, with the proviso that the total of i), ii) and iii) corresponds to 100% by weight and the solubility in a phosphate buffer solution at a pH of 6.8 under standard conditions is such that when a 0.3% by weight aqueous preparation of the terpolymer is filtered through a membrane filter having an average pore size of 8 μm, the content of insoluble matter remaining on the filter is less than or equal to 25% by weight of the amount of terpolymer in the aqueous preparation.

[0012] The present invention further relates to a method for making the terpolymers of the present invention by free radical initiated polymerization of a monomer mixture of three different monomers to provide the terpolymer.

[0013] In all embodiments of the present invention, acrylic acid may undergo polymerization either in the free acid form, or as sodium or potassium acrylate (calculated as acrylic acid), or mixtures thereof.

[0014] The N-vinyl lactam may be N-vinyl pyrrolidone or N-vinyl caprolactam, preferably N-vinyl pyrrolidone, most preferably N-vinyl caprolactam.

[0015] Another aspect of the present invention is the use of a terpolymer to inhibit the in vivo recrystallization of an active ingredient after release from a dosage form into the aqueous environment of the human or animal body, each dosage form comprising a terpolymer and an active ingredient, the active ingredient having a solubility in water under standard conditions of less than 0.1% by weight.Preferably, the solubility in water of the active ingredient under standard conditions is less than 0.05% by weight, and the active ingredient is present in such dosage form in an amorphous state or is molecularly dispersed.Amorphous means that less than 5% by weight is crystalline.The crystalline ratio can be measured by X-ray diffraction.

[0016] In the present invention, solubilities (whether in water, phosphate buffer or other appropriate biologically relevant systems) are always those at standard conditions, i.e., a temperature of 23° C. and a pressure of 0.101325 MPa.

[0017] Solubility in phosphate buffer at pH 6.8 is maintained under standard conditions by preparing an aqueous preparation of the terpolymer in water. When a 0.3 wt.% aqueous preparation of the terpolymer is filtered through a membrane filter with an average pore size of 8 μm, the content of insoluble material remaining on the filter is not more than 25 wt.% of the amount of terpolymer in the aqueous preparation. The membrane filter is preferably a polycarbonate filter membrane. Such membranes are commercially available. Preferably, the residue is less than 10 wt.%.

[0018] According to the invention, a poorly water-soluble active ingredient is one which has a solubility in water of less than 0.1% by weight under standard conditions.

[0019] As already mentioned, terpolymers suitable for the water-soluble formulation of poorly water-soluble active ingredients are terpolymers having a solubility in phosphate buffer at pH 6.8 as defined above, obtained by free radical initiated polymerization of a monomer mixture of three different monomers to give a terpolymer, in which i) 20-35% by weight of the structural units are derived from acrylic acid, ii) 45-60% by weight of the structural units are derived from hydrophobic methacrylates, and iii) 15-40% by weight of the structural units are derived from a third olefin monomer selected from the group consisting of N-vinyllactam, hydroxyethyl methacrylate and phenoxyethyl acrylate, with the proviso that the total of i), ii) and iii) corresponds to 100% by weight, and the poorly water-soluble active ingredient has a solubility of less than 0.1% by weight in water, simulated intestinal fluid or gastric fluid. The N-vinyllactam may be N-vinylpyrrolidone or N-vinylcaprolactam, preferably N-vinylpyrrolidone, most preferably N-vinylcaprolactam.

[0020] Preferred are polymers having a solubility in phosphate buffer at a pH of 6.8 as defined above, obtained by free radical initiated polymerization of a monomer mixture of three different monomers to give a terpolymer, in which i) 20-35% by weight of the structural units are derived from acrylic acid, ii) 45-55% by weight of the structural units are derived from a hydrophobic methacrylate selected from the group consisting of isopropyl methacrylate, tert-butyl methacrylate and cyclohexyl methacrylate, and iii) 20-35% by weight of the structural units are derived from a third olefin monomer selected from the group consisting of N-vinyl lactam, hydroxyethyl methacrylate and phenoxyethyl acrylate, with the proviso that the total of i), ii) and iii) corresponds to 100% by weight. The N-vinyl lactam may be N-vinyl pyrrolidone or N-vinyl caprolactam, preferably N-vinyl pyrrolidone, most preferably N-vinyl caprolactam.

[0021] In all embodiments of the present invention, amounts for monomer-derived moieties given as weight percent are intended to include a deviation of ±1% by weight.

[0022] The polymers can be prepared in a manner conventional per se by free radical polymerization. The polymerization is preferably carried out as a solution polymerization in an organic solvent, preferably in an alcohol, such as methanol or ethanol, in particular in isopropanol. Such a method is known per se to those skilled in the art. Suitable initiators are, for example, organic peroxides, such as diisobutyryl peroxide, 1,1,3,3-tetramethylbutyl peroxy neodecanoate, tert-amyl peroxy neodecanoate, tert-butyl peroxy neodecanoate, tert-butyl peroxy neoheptanoate, tert-butyl peroxy pivalate, tert-butyl peroxy-2-ethylhexanoate and di-tert-butyl peroxide. Preference is given to tert-butyl peroxy pivalate, tert-butyl peroxy-2-ethylhexanoate and tert-butyl peroxy neodecanoate. Alternatively, alcohol soluble azo initiators, particularly those that do not form physiologically significant by-products, such as dimethyl 2,2'-azobis(2-methylpropionate), can be used to initiate polymerization.

[0023] The polymerization may be carried out at temperatures between 20 and 150° C., preferably between 50 and 130° C. The polymerization can be carried out both under atmospheric pressure or in a closed reactor under elevated pressure. In this case, it is possible to polymerize under a pressure set during the reaction or the pressure can be adjusted by injecting or evacuating gas.

[0024] It is also possible to carry out the polymerization in the presence of a chain transfer agent, for example ethylhexyl thioglycolate.

[0025] The polymerization can be carried out continuously, semi-batch or as a batch process, the polymer being preferably obtained by a feed process.

[0026] The polymer is typically partially neutralized with an aqueous alkaline solution after the polymerization process. The degree of neutralization is adjusted so that the pH of the aqueous solution of the partially neutralized terpolymer is in the range of 5 to 9. Suitable aqueous alkaline solutions are sodium hydroxide or potassium hydroxide solutions.

[0027] Conversion of the polymer solution into a solid form may be carried out by conventional drying processes, such as spray drying, freeze drying or roller drying.

[0028] According to a preferred embodiment, the organic solvent is removed by steam distillation to yield an aqueous solution of the polymer, which can then be spray dried to the respective powder.

[0029] According to another preferred embodiment, the organic reaction solution of the polymer is directly treated with the active ingredient to give a solid dispersion.

[0030] The weight average molecular weight of the terpolymer, as measured by gel permeation chromatography, is in the range of 7,000 to 100,000 g / mol, preferably 7,000 to 70,000 g / mol, and most preferably 10,000 to 50,000 g / mol.

[0031] The glass transition temperature, calculated according to the Fox formula, is in the range of >80° C., preferably higher than 100° C., up to 150° C.:

[0032]

number

[0033] The glass transition temperature may also be determined by differential scanning calorimetry at a heating rate of 20 K / min. The measurement can be carried out in accordance with DIN EN ISO 11357-2.

[0034] The active ingredient may be selected from the group of pharmaceutical, nutritional or agrochemical active ingredients.

[0035] Examples which may be mentioned here are antihypertensive drugs, vitamins, cytostatics, especially taxol, anesthetics, neuroleptics, antidepressants, antibiotics, antifungals, fungicides, chemotherapeutic drugs, urological drugs, platelet aggregation inhibitors, sulfonamides, antispasmodics, hormones, immunoglobulins, serum, thyroid medications, psychoactive drugs, Parkinson's drugs and other antihyperactivity drugs, ophthalmic drugs, neuropathic preparations, calcium metabolism regulators, muscle relaxants, narcotics, antihyperlipidemic drugs, liver medications, coronary artery drugs, cardiac drugs, immunotherapeutic drugs, regulatory peptides and their inhibitors, hypnotics, sedatives, gynecological drugs, medications for gout, fibrinolytic drugs, enzyme preparations and and transport proteins, enzyme inhibitors, emetics, weight loss drugs, perfusion enhancers, diuretics, diagnostics, corticoids, cholinergics, biliary tract drugs, antiasthmatics, broncholytics, beta-receptor blockers, calcium antagonists, ACE inhibitors, arteriosclerosis drugs, anti-inflammatory drugs, anticoagulants, antihypotensives, antihypoglycemic drugs, antihypertensives, antifibrinolytics, antiepileptics, antiemetics, antidotes, antidiabetics, antiarrhythmics, antianemics, antiallergics, anthelmintics, analgesics, stimulants, aldosterone antagonists, or antiviral active ingredients, or active ingredients for the treatment of HIV infection and AID syndrome.

[0036] The terpolymers of the invention are preferably used to prepare formulations with active ingredients that are poorly soluble in water.

[0037] The formulation may be either a true solution, where both the active ingredient and the terpolymer of the invention are dissolved in a suitable solvent or mixture of solvents, or a solid dispersion, where the active ingredient is embedded in an amorphous form in a solid polymer matrix. A solid dispersion is a dispersion of one or more active ingredients in a solid polymer matrix [WL Chiou, S. Riegelman, Pharmaceutical applications of solid dispersion systems, Journal of Pharmaceutical Sciences, 60 (1971) 1281-1302]. A solid dispersion may be prepared by heating a physical mixture of the active ingredient and the polymer until it melts, followed by cooling and solidification (melt method). Alternatively, a solid dispersion may be prepared by dissolving a physical mixture of the active ingredient and the polymer in a common solvent, followed by evaporation of the solvent (solvent method). A solid dispersion may contain an active ingredient molecularly dispersed in a crystalline matrix. Alternatively, a solid dispersion may consist of an amorphous carrier; the active ingredient may be molecularly dispersed in the carrier or may form an amorphous precipitate. In either case, the active ingredient must be in amorphous form. By "amorphous" it is meant that less than 5% by weight of the active ingredient is crystalline.

[0038] According to one embodiment of the present invention, the solid dispersion according to the present invention can be prepared by the solvent method. The active ingredient and the polymer are dissolved in an organic solvent or solvent mixture, and then the solution is dried. Dissolution can also take place at elevated temperature (30-150°C) and under pressure.

[0039] Suitable organic solvents are dimethylformamide, methanol or mixtures thereof, and mixtures with tetrahydrofuran.Suitable organic solvents also include ethanol, isopropanol, dimethylacetamide, acetone and / or dioxane.These solvents or solvent mixtures may further contain up to 20% by weight of water.

[0040] In principle all types of drying are possible: spray drying, fluidized bed drying, drum drying, freeze drying, vacuum drying, belt drying, roller drying, carrier gas drying, evaporation, etc.

[0041] According to another embodiment of the invention, the solid dispersion is prepared by a melting process. The active ingredient is mixed with the polymer. The formation of the solid dispersion is carried out by heating to a temperature of 50-180 ° C. Here, temperatures above the glass transition temperature of the polymer or above the melting point of the active ingredient are advantageous. By adding softening auxiliaries, such as water, organic solvents, conventional organic softeners, it is possible to correspondingly reduce the processing temperature. Auxiliaries that can be evaporated again very easily later, i.e. have a boiling point below 180 ° C, preferably below 150 ° C, are particularly advantageous.

[0042] According to a preferred embodiment, this type of preparation is carried out in a screw extruder, where the process parameters which have to be individually adjusted can be determined by the person skilled in the art by simple experiments within the scope of conventional expertise.

[0043] According to a preferred embodiment, the softener is added during melting. Preferred softeners are citrate esters, such as triethyl citrate or acetyl tributyl citrate, glycol derivatives, such as polyethylene glycol, propylene glycol or poloxamers; castor oil and mineral oil derivatives; sebacate esters, such as dibutyl sebacate, triacetin, fatty esters, such as glycerol monostearate, fatty alcohols, such as stearyl alcohol, fatty acids, such as stearic acid, ethoxylated oils, ethoxylated fatty acids, ethoxylated fatty alcohols or vitamin E TPGS (tocopherol polyethylene glycol succinate). Softeners may be used in amounts of 0.1 to 40% by weight, preferably 1 to 20% by weight, based on the polymer.

[0044] The solid dispersions produced are amorphous. The amorphous state can be established by X-ray diffraction. The so-called "X-ray amorphous" state of a solid dispersion means that the proportion of crystals is less than 5% by weight.

[0045] The amorphous state can also be investigated using DSC thermograms (differential scanning calorimetry). The solid dispersions according to the invention do not have a melting peak, but only a glass transition temperature, which also depends on the type of active ingredient used in the solid dispersion according to the invention. The glass transition temperature is measured at a heating rate of 20 K / min.

[0046] In the course of the preparation of the dosage forms according to the invention, customary pharmaceutical auxiliaries may optionally be processed simultaneously, which are selected from the classes of adsorbents, binders, disintegrants, dyes, fillers, flavorings or sweeteners, glidants, lubricants, preservatives, softeners, solubilizers, solvents or cosolvents, stabilizers (e.g. antioxidants), surfactants, or wetting agents.

[0047] The novel terpolymers make it possible to inhibit the recrystallization of the active pharmaceutical ingredient in the aqueous medium of the gastrointestinal tract after release of the active ingredient from a dosage form in which the active ingredient is present in the form of an amorphous solid dispersion of the active ingredient in the polymer matrix of the novel terpolymer or in the form of a liquid solution of the active ingredient and the terpolymer of the invention in a suitable solvent vehicle system. EXAMPLES

[0048] Abbreviation VP: N-vinylpyrrolidone HEMA: 2-hydroxyethyl methacrylate POEA: Phenoxyethyl acrylate tBMA: tert-butyl methacrylate CHMA: Cyclohexyl methacrylate IPMA: Isopropyl methacrylate VC: N-vinylcaprolactam AA: Acrylic acid

[0049] Explanation of the GPC method The molecular weights of the polymers were determined by size exclusion chromatography (SEC) at 35 °C using dimethylacetamide containing 1 wt % trifluoroacetic acid and 0.5 wt % lithium bromide as eluent, narrow molecular weight distribution poly(methyl methacrylate) standards (commercially available from PSS Polymer Standard Solutions GmbH, with molecular weights ranging from M = 800 to M = 2,200,000) and a differential refractive index (DRI) detector from a DRI Wyatt Optilab DSP.

[0050] Solubility in phosphate buffer solutions: Test method description 300 mg of dried polymer was added to 100 mL of phosphate buffer (pH 6.8) in a 150 mL glass screw-cap bottle. The mixture was stirred at 300 rpm for 15 min at 23 °C using a magnetic stirrer and a 3-5 cm long magnetic stir bar. The mixture was then filtered through a dried and weighed polycarbonate filter (available from Whatman) with a diameter of 47 mm and an average pore size of 8 μm. The filter with the residue was dried overnight at 75 °C in a vacuum oven at 0.02 MPa. The amount of residue on the filter was determined by subtracting the weight of the dry filter from the weight of the dry filter containing the residue. The amount of residue is given as a percentage of the total amount of polymer (300 mg).

[0051] The glass transition temperatures were calculated according to the Fox equation using the homopolymer Tg values ​​shown in Table 1.

[0052]

number

[0053] [Table 1]

[0054] Residual monomer amount The contents of VP, AA and VC were determined by reversed-phase liquid chromatography using UV detection at absorption wavelengths of 235 nm for VP and 205 nm for AA and VC. Quantification was performed by external calibration. An aliquot of the sample was dissolved in methanol and injected directly. Chromatographic separation was achieved by using gradient elution.

[0055] The contents of HEMA, tBMA, POEA, CHMA and IPMA were determined by capillary gas chromatography using a flame ionization detector (FID). Quantitation was performed by standard addition. An aliquot of the sample was dissolved in 2-propanol and injected into a non-polar capillary column coated with a stationary phase of dimethylpolysiloxane.

[0056] Polymer synthesis Polymer A1 A 2-liter glass reactor equipped with a mechanical stirrer, condenser, nitrogen sweep, thermometer, and inlets for the gradual addition of monomer and initiator was charged with 240 grams of isopropanol. A monomer solution was prepared by dissolving 75 grams of acrylic acid, 165 grams of tert-butyl methacrylate, and 60 grams of N-vinylpyrrolidone in 266 grams of isopropanol. An initiator solution was prepared by dissolving 3.84 grams of tert-butyl peroxypivalate solution (75 wt % in mineral spirits) in 200 grams of isopropanol. A total of 10 wt % of the monomer solution was added to the reactor charge, and the resulting solution was heated to 75° C. with stirring at 100 rpm. Then, a total of 10 wt % of the initiator solution was added, and the temperature was increased to 80° C. The remaining 90 wt % of the monomer and initiator solutions were then added separately at constant feed rates to the stirred reactor charge over 4 and 5 hours, respectively. The temperature of the reaction mixture was maintained at 80° C. during these additions. After the additions were complete, the reaction mixture was stirred at 80° C. for an additional hour and then allowed to cool to ambient temperature. A sample was taken from the mixture and dried for SEC measurement. Another sample was taken for residual monomer content measurement. Approximately 150 ml of water was added, after which the pH of the reaction mixture was set by adding 25 wt % aqueous sodium hydroxide solution. Volatiles were removed and the product was dried overnight in a vacuum oven at 75° C. and 0.02 MPa.

[0057] Polymers B1 and C1 were prepared similarly to polymer A1.

[0058] The variations are shown in Table 1.

[0059] [Table 2]

[0060] Polymer A3 A 2-liter glass reactor equipped with a mechanical stirrer, condenser, nitrogen sweep, thermometer, and inlets for the gradual addition of monomer and initiator was charged with a solution of 60 grams of N-vinylpyrrolidone in 150 grams of isopropanol. A monomer solution was prepared by dissolving 75 grams of acrylic acid and 165 grams of tert-butyl methacrylate in 152 grams of isopropanol, and an initiator solution was prepared by dissolving 4.0 grams of tert-butyl peroxypivalate solution (75 wt % in mineral spirits) in 150 grams of isopropanol. A total of 10 wt % of the monomer solution was added to the reactor charge, and the resulting solution was heated to 70° C. with stirring at 100 rpm. Then, a total of 10 wt % of the initiator solution was added, and the temperature was increased to 75° C. The remaining 90 wt % of the monomer and initiator solutions were then added separately at constant feed rates to the stirred reactor charge over 4 and 6 hours, respectively. The temperature of the reaction mixture was maintained at 75° C. during these additions. After the additions were complete, the reaction mixture was stirred at 75° C. for an additional hour and then allowed to cool to ambient temperature. A sample was taken from the mixture and dried for SEC measurement. Another sample was taken for residual monomer content measurement. Approximately 150 ml of water was added, after which the pH of the reaction mixture was set by adding 25 wt. % aqueous sodium hydroxide solution. The pH of the reaction mixture was set by adding 25 wt. % aqueous sodium hydroxide solution. The volatiles were removed under reduced pressure and the product was dried overnight in a vacuum oven at 75° C. and 0.02 MPa.

[0061] Polymers A2 and A4-A8 were prepared similarly to Polymer A3. Polymer A8 was prepared using 4.0 g of dimethyl 2,2'-azobis(2-methylpropionate) instead of 4.0 grams of tert-butyl peroxypivalate solution. The variations are shown in Table 3.

[0062] [Table 3]

[0063] Polymers C2, C3, C4, D1, E1 and F1 were prepared similarly to polymer A3. Polymer C3 was prepared without VP in the pre-feed charge and with 60 g POEA in the monomer feed. Polymer D1 was prepared with 165 g CHMA instead of 165 g tBMA in the monomer feed. Polymer E1 was prepared with 165 g IPMA instead of 165 g tBMA in the monomer feed. Polymer F1 was prepared with VC instead of VP. As with VP, VC was included in the pre-feed charge. Polymer F1 was synthesized with 300 g isopropanol instead of 150 g in the pre-feed charge and 255 g isopropanol instead of 152 g in the monomer feed. The variations are summarized in Table 4.

[0064] [Table 4]

[0065] The amount of residue is given as a percentage of the total amount of polymer used in the described solubility test. The results are listed in Table 5.

[0066] [Table 5]

[0067] Preparation of amorphous solid dispersions by spray drying Celecoxib - Polymer formulation (10% drug loading by weight): The solid dispersion consisted of celecoxib and polymer A7. To prepare the formulation, 3.0 g of celecoxib and 27.0 g of polymer were dissolved in 570 g of methanol (5 wt% solids). Spray drying was performed on a Buchi Mini Spray Dryer B-290 equipped with a 0.7 mm two-fluid nozzle under the following conditions: Nitrogen flow rate 35m 3 / h Inlet temperature 85~105℃ Outlet temperature 50~70℃ Spray pressure 0.7MPa Liquid flow rate 300g / h

[0068] The product was collected using a cyclone. The drug content of the spray-dried formulations was determined by measuring UV absorption at 252 nm; solid state properties were analyzed using powder X-ray diffraction (PXRD): Drug content (UV spectroscopy) 10.3-10.7% by weight Solid state properties (PXRD) X-ray amorphous

[0069] Celecoxib - Polymer formulation (25% drug loading by weight): The solid dispersions consisted of celecoxib and Polymer A1, Polymer A2, Polymer A3, Polymer A4, Polymer A5, Polymer A6, Polymer A7, Polymer A8, Polymer B1, Polymer C1, Polymer C2, Polymer C3, Polymer C4, Polymer D1, Polymer E1, Polymer F1, HPMCAS-LF, HPMCAS-MF or HPMCAS-HF. To prepare the formulations, 2.5 g of celecoxib and 7.5 g of polymer were dissolved in 190 g of methanol or a 1:1 mixture of methanol and tetrahydrofuran (5 wt% solids). Spray drying was performed on a Buchi Mini Spray Dryer B-290 equipped with a 0.7 mm two-fluid nozzle under the following conditions: Nitrogen flow rate 35m 3 / h Inlet temperature 85~105℃ Outlet temperature 50~70℃ Spray pressure 0.7MPa Liquid flow rate 300g / h

[0070] The product was collected using a cyclone. The drug content of the spray-dried formulations was determined by measuring UV absorption at 252 nm; solid state properties were analyzed using powder X-ray diffraction (PXRD): Drug content (UV spectroscopy) 24.2-27.6% by weight Solid state properties (PXRD) X-ray amorphous

[0071] Danazol-polymer formulation (10% drug loading by weight): The solid dispersions consisted of danazol and Polymer A1, Polymer A2, Polymer A3, Polymer A4, Polymer A5, Polymer A6, Polymer A7, Polymer A8, Polymer B1, Polymer C1, Polymer C3, Polymer D1, Polymer E1, Polymer F1, HPMCAS-LF, HPMCAS-MF or HPMCAS-HF. To prepare the formulations, 1.5 g of danazol and 13.5 g of polymer were dissolved in 285 g of methanol or a 1:1 mixture of methanol and tetrahydrofuran (5 wt. % solids). Spray drying was carried out on a Buchi Mini Spray Dryer B-290 equipped with a 0.7 mm two-fluid nozzle under the following conditions: Nitrogen flow rate 35m 3 / h Inlet temperature 85~105℃ Outlet temperature 50~70℃ Spray pressure 0.7MPa Liquid flow rate 300g / h

[0072] The product was collected using a cyclone. The drug content of the spray-dried formulations was determined by measuring UV absorption at 286 nm; solid state properties were analyzed using powder X-ray diffraction (PXRD): Drug content (UV spectroscopy) 9.4-11.7% by weight Solid state properties (PXRD) X-ray amorphous

[0073] In vitro release experiments Preparation of Phosphate Buffer pH 6.8 To prepare 5 L of phosphate buffer pH 6.8, 34.025 g of potassium dihydrogen phosphate was placed in a 5 liter volumetric flask and dissolved in approximately 1 L of water. 112 mL of 1 M sodium hydroxide solution was then added; the solution was diluted to 5 L with water. If necessary, the pH of the solution was adjusted to 6.8.

[0074] Dissolution test in phosphate buffer pH 6.8 In vitro dissolution tests were performed to quantify drug release and measure the maintenance of supersaturation. For this purpose, 100 mL of phosphate buffer pH 6.8 was placed in an Erlenmeyer flask and placed on a multi-position magnetic stirrer (stirring speed approximately 300 rpm). After reaching a temperature of 37°C, a defined amount of the spray-dried formulation (corresponding to a drug concentration of 0.14 mg / ml) was added. Samples of 1000 μL were removed after 5, 15, 30, 60, 90, 120, 180, 240, 300 and 360 minutes. Samples were pipetted into microcentrifuge tubes and centrifuged at 14,680 rpm for 3 minutes to remove precipitates. The clear supernatant was diluted with methanol (1:4 or 1:10 depending on the drug concentration); the concentration of the drug in the solution was determined by UV spectroscopy using a calibration curve of pure drug in methanol. To evaluate the performance of the polymers, the area under the concentration-time curve (AUC) was calculated as follows:

[0075]

number

[0076] [Table 6]

[0077] [Table 7] (Additional Note) (Appendix 1) A terpolymer in which 20 to 35% by weight of the structural units are derived from acrylic acid, 45 to 60% by weight of the structural units are derived from a hydrophobic methacrylate selected from the group consisting of isopropyl methacrylate, tert-butyl methacrylate, and cyclohexyl methacrylate, and 15 to 40% by weight of the structural units are derived from a third olefin monomer selected from the group consisting of N-vinyl lactam, hydroxyethyl methacrylate, and phenoxyethyl acrylate, with the total amount of structural units derived from the three monomer groups being 100% by weight. (Appendix 2) 2. A terpolymer according to claim 1, whose solubility in phosphate buffer of pH 6.8 under standard conditions is such that when a 0.3 wt. % aqueous preparation of the terpolymer is filtered through a membrane filter having an average pore size of 8 μm, the content of insoluble matter remaining on the filter is not more than 25 wt. % of the amount of terpolymer in the aqueous preparation. (Appendix 3) 3. The terpolymer of claim 1 or 2, wherein the hydrophobic methacrylate is tert-butyl methacrylate. (Appendix 4) 4. The terpolymer according to any one of claims 1 to 3, wherein the N-vinyl lactam is N-vinyl pyrrolidone. (Appendix 5) 4. The terpolymer according to any one of claims 1 to 3, wherein the N-vinyl lactam is N-vinyl caprolactam. (Appendix 6) 6. The terpolymer according to any one of claims 1 to 5, having a calculated glass transition temperature in the range of 80 to 150°C. (Appendix 7) 6. The terpolymer according to any one of claims 1 to 5, having a calculated glass transition temperature in the range of 100 to 150°C. (Appendix 8) 8. The terpolymer according to any one of claims 1 to 7, wherein the amount of structural units derived from tert-butyl methacrylate is in the range of 45 to 55% by weight. (Appendix 9) 9. The terpolymer according to any one of claims 1 to 8, wherein the amount of structural units derived from acrylic acid is in the range of 20 to 30% by weight. (Appendix 10) 10. The terpolymer according to any one of claims 1 to 9, wherein the amount of structural units derived from the third olefin monomer is in the range of 20 to 35% by weight. (Appendix 11) 11. The terpolymer according to any one of claims 1 to 10, having a weight average molecular weight in the range of 7,000 to 100,000 g / mol. (Appendix 12) 12. The terpolymer of any one of claims 1 to 11, which is partially neutralized to provide a pH in the range of 5 to 9 upon dissolution in water. (Appendix 13) A process for producing a terpolymer according to any one of claims 1 to 12 by radical polymerization of monomers in the presence of a free radical initiator. (Appendix 14) 14. The method of claim 13, wherein the polymerization is a solution polymerization. (Appendix 15) 15. The method of claim 13 or 14, wherein the solution polymerization is carried out in an organic solvent. (Appendix 16) 16. The method of claim 15, wherein the organic solvent is isopropanol. (Appendix 17) 17. The method according to any one of claims 13 to 16, wherein the radical initiator is a peroxide. (Appendix 18) 18. A pharmaceutical dosage form comprising a terpolymer according to any one of claims 1 to 17 and an active pharmaceutical ingredient having a solubility in water under standard conditions of less than 0.1% by weight, wherein the active ingredient is present in amorphous form. (Appendix 19) 18. Use of a terpolymer according to any one of appendixes 1 to 17 as a recrystallization inhibitor in a pharmaceutical dosage form for inhibiting the recrystallization in the aqueous environment of the human or animal body of an active ingredient having a solubility in water under standard conditions of less than 0.1% by weight, wherein the active ingredient is present in the pharmaceutical dosage form in amorphous form.

Claims

1. 1. A terpolymer having 20-35% by weight of structural units derived from acrylic acid, 45-60% by weight of structural units derived from a hydrophobic methacrylate selected from the group consisting of isopropyl methacrylate, and cyclohexyl methacrylate, and 15-35% by weight of structural units derived from a third olefin monomer selected from the group consisting of N-vinyl lactam, hydroxyethyl methacrylate, and phenoxyethyl acrylate, with the proviso that the total amount of structural units derived from the three monomer groups totals 100% by weight, which terpolymer has been partially neutralized to provide a pH in the range of 5-9 upon dissolution in water.

2. 2. The terpolymer according to claim 1, whose solubility in a phosphate buffer solution of pH 6.8 under standard conditions is such that when a 0.3% by weight aqueous preparation of the terpolymer is filtered through a membrane filter having an average pore size of 8 μm, the content of insoluble matter remaining on the filter is not more than 25% by weight of the amount of terpolymer in the aqueous preparation.

3. 3. The terpolymer of claim 1, wherein the N-vinyl lactam is N-vinyl pyrrolidone.

4. 3. The terpolymer of claim 1, wherein the N-vinyl lactam is N-vinyl caprolactam.

5. The terpolymer of any one of claims 1 to 4, having a calculated glass transition temperature in the range of 80 to 150°C.

6. The terpolymer of any one of claims 1 to 4, having a calculated glass transition temperature in the range of 100 to 150°C.

7. 7. The terpolymer according to claim 1, wherein the amount of structural units derived from acrylic acid is in the range of 20 to 30% by weight.

8. The terpolymer of any one of claims 1 to 7, wherein the amount of structural units derived from the third olefin monomer is in the range of 20 to 35 wt%.

9. 9. The terpolymer according to claim 1, having a weight average molecular weight in the range of 7,000 to 100,000 g / mol.

10. A process for preparing the terpolymers according to any one of claims 1 to 9 by radical polymerization of monomers in the presence of a free radical initiator.

11. The method of claim 10, wherein the polymerization is a solution polymerization.

12. 12. The process according to claim 10 or 11, wherein the solution polymerization is carried out in an organic solvent.

13. The method of claim 12, wherein the organic solvent is isopropanol.

14. The method according to any one of claims 10 to 13, wherein the radical initiator is a peroxide.

15. 10. A pharmaceutical formulation comprising a terpolymer according to any one of claims 1 to 9 and an active pharmaceutical ingredient having a solubility in water at standard conditions of less than 0.1% by weight, wherein the active ingredient is present in amorphous form.

16. 10. Use of the terpolymer according to any one of claims 1 to 9 as a recrystallization inhibitor in a pharmaceutical formulation for inhibiting the recrystallization in the aqueous environment of the human or animal body of an active ingredient having a solubility in water under standard conditions of less than 0.1% by weight, wherein the active ingredient is present in the pharmaceutical formulation in amorphous form.

Citation Information

Patent Citations

  • Ternary copolymer and use

    JP1988048315A

  • Color filter and its production

    JP1994273612A

  • Terpolymer

    JP1994340721A

  • amphoteric anionic copolymer

    JP2007514030A